A bayesian way to correct for measurement error in drug risk estimates from EHR data. (2018) - Lavigne, Maxime; Goulden, Robert; Habib, Bettina; Joseph, Lawrence; Girard, Nadyne; Buckeridge, David; Tamblyn, Robyn
No abstract available